The Impact of the Covid-19 Pandemic on the Development of Russian National Economy Sectors: Analysis of Dynamics and Search for Stabilization Measures - Evgeniya K. KARPUNINA; Larisa M. BUTOVA; Tatyana G. SOBOLEVSKAYA; Evgeniya A. BADOKINA; Oksana V. PLIUSNINA (Communications of International Proceedings, 2021)
The purpose of the study is to analyze the dynamics of the development of Russian economic sectors during the COVID-19 pandemic, as well as to identify the most affected sectors of the national economy. The article presents a general description of the socio-economic situation in the world in terms of the COVID-19 pandemic, with an emphasis on some developed countries. The Russian specifics of the course of the pandemic and the appearance of its negative consequences for the economy and society are determined. The implemented system measures of state support for enterprises of the real sector of the economy in Russia are studied.  China's experience in overcoming the negative consequences of the coronavirus pandemic for economic sectors is studied, and the most effective measures of macroeconomic anti-crisis regulation are systematized. The study of the system of deterrence sharp drop in business activity and ensuring a smooth exit from the “corkscrew” decline in GDP in strategic sectors of the Russian economy, the authors offer concrete steps for adjusting economic policy in the conditions of Russian reality with the Chinese experience.
Keywords: socio-economic development; COVID-19 pandemic; economic sectors; lockdown; recession; economic growth; public policy